Formulation and Physical Assessment of Different Topical Products using Bandotan Herb (Ageratum conyzoides L.) Extract - Andriani, Disa; Pratimasari, Diah (GLOBAL HEALTH SCIENCE GROUP, 2024)
Bandotan (Ageratum conyzoides L.) is one of the Asteraceae family plants that has bioactive compound components in the form of polyphenol compounds, terpenoids, and alkaloids. 70% ethanol extract of bandotan herb (Ageratum conyzoides L.) is known to have antioxidant activity. This makes herba bandotan has the potential to be develooped into cosmetic preparations to prevent premature aging of the skin. This study aims to determine the herba bandotan topical preparation that has the best physical properties. Bandotan herb was extracted with 70% ethanol in the amount of 1: 10 at 28˚C for 24 hours using the shaking method at 100 rpm. The ethanol liquid filtrate obtained was then evaporated to obtain a thick extract. Thick bandotan extract is then made into gel, cream, and lotion preparations and evaluated. The resulting % yield of bandotan herb extract was 11.3%. The concentration of 1%, 3% and 5% bandotan herb active substances in the preparation affects the organoleptics, viscosity, spreadability and adhesiveness of the preparation. The best topical preparations of bandotan herb extract that meet the requirements of the pH test, viscosity test, spreadability test, and adhesion test is cream preparations.